A Philosopher Looks at The Impacts of Pollution on Health - Attfield, Robin (Studia Ecologiae et Bioethicae, 2026)
This study of the impacts of pollution on health opens with a discussion on the role of applied ethics when such issues are considered, which includes seeking clarity and presenting the case for ethical obligations at levels ranging from that of individuals via companies to governments and inter-governmental co-operation. This approach is then applied to issues of air pollution from nitrogen dioxide and particulates, as in my book The Ethics of the Climate Crisis (Attfield 2024), and then to issues surrounding microplastics and other global issues of pollution (such as that of carbon monoxide). It is also applied to more local issues, such as the impacts of desert sand on locations like Beijing, of photochemical smog on Los Angeles, and of chemical dumping on the coast of East Africa. Some ethical findings are also conveyed. Normative solutions considered for air pollution include the replacement of petrol- and diesel-powered vehicles with electric vehicles, and (meanwhile) the introduction of congestion charges and of zones that only vehicles with low emissions are allowed to enter. Solutions considered to counter plastic pollution include recycling schemes and public encouragement for plastics manufacturers to make use of alternatives to plastic. Generally, internationally agreed regulation is also needed.